2015
DOI: 10.1108/intr-09-2013-0199
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of valence and attributes of e-WOM on consumer judgment for message and product

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 52 publications
(116 reference statements)
3
99
1
3
Order By: Relevance
“…Studies propose that message, source of information and reviewer characteristics affect perceived eWOM helpfulness and credibility [5,13]. Also, it is found that the effectiveness of eWOM communications can be moderated by platform type and type of product [9]. Determinants of eWOM persuasiveness are presented in Table 1 and briefly discussed below.…”
Section: Persuasiveness Of Ewom Communicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies propose that message, source of information and reviewer characteristics affect perceived eWOM helpfulness and credibility [5,13]. Also, it is found that the effectiveness of eWOM communications can be moderated by platform type and type of product [9]. Determinants of eWOM persuasiveness are presented in Table 1 and briefly discussed below.…”
Section: Persuasiveness Of Ewom Communicationsmentioning
confidence: 99%
“…Researchers suggest that consumers rely on eWOM communications if they perceive them persuasive [6]. Studies on the persuasiveness of eWOM mostly use the Elaboration Likelihood Model [7][8][9][10][11][12]. In order to be persuasive, message should be considered as helpful and credible.…”
Section: Persuasiveness Of Ewom Communicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jeong and Koo [34] had studied the effect the valence and objectivity of the online review on the judgment of consumers and if eWOM had a moderating impact on this. The authors tried to check the moderating effect various online platforms like company operated community or consumer operated.…”
Section: Word Of Mouthmentioning
confidence: 99%